The Vulnerable Consumer in E-Commerce - Vartavan Ghazvini, Nasim (Res Severa Verum Gaudium, 2020)
This article analyses the different types of the consumer model and classifies the consumer in E-Commerce. The European consumer model doesn’t protect the vulnerable consumers completely. Therefore it is necessary to illustrate the need for protection of the vulnerable consumer, especially in the E-Commerce. A big problem occurs based on an over-information because of the information obligation of the companies. Furthermore the right of withdrawal is difficult in the case of downloading a digital software and an improvement is necessary. Lastly this article shows the 2012 Button-Solution.